2006
DOI: 10.1149/1.2354454
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Copper on Oxidized Ruthenium

Abstract: Ruthenium is an alternative liner material for copper metallization. We report on the nucleation and growth of copper on ruthenium in acidified copper sulfate solution and explore the influence of the PEG-Cl-SPS additive system. We show that the physical vapor deposition ruthenium has an oxide layer approximately 1 nm thick. The additives and copper concentration have a relatively small influence on island density but a significant influence on the island morphology. Without additives, both randomly oriented h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 24 publications
2
43
0
Order By: Relevance
“…Early work suggested a group of noble metals (i.e., Pt, Pd, Ru, Rh, Ir, Ag, Te, and Tc) [169] that could be suitable for direct Cu deposition from acidic Cu sulfate solutions. Cu seedless superfill of sub-100-nm features was demonstrated so far for Ru [169][170][171][172][173][174], Os [175], and Ir [176] (Table 27.6). Among these candidates Ru has attracted most of the interest as a new barrier material owing to its favorable intrinsic properties such as electrical and thermal conductivity that are twice as large as those of Ta.…”
Section: New Barrier Materialsmentioning
confidence: 75%
See 1 more Smart Citation
“…Early work suggested a group of noble metals (i.e., Pt, Pd, Ru, Rh, Ir, Ag, Te, and Tc) [169] that could be suitable for direct Cu deposition from acidic Cu sulfate solutions. Cu seedless superfill of sub-100-nm features was demonstrated so far for Ru [169][170][171][172][173][174], Os [175], and Ir [176] (Table 27.6). Among these candidates Ru has attracted most of the interest as a new barrier material owing to its favorable intrinsic properties such as electrical and thermal conductivity that are twice as large as those of Ta.…”
Section: New Barrier Materialsmentioning
confidence: 75%
“…In a separate study of nucleation and growth kinetics of Cu on air-oxidized PVD, Ru has been shown to have very rapid nucleation with nucleation density that is exponentially dependent upon the growth overpotential [171]. Although these results suggest that the concentration of additives and Cu 2 þ ions in the solution do not influence the island distribution, these concentrations affect the island shape.…”
Section: New Barrier Materialsmentioning
confidence: 93%
“…However, this report does not give information on the quality of the interface, and in particular not about the presence or absence of ruthenium oxide layer. A method for the electrochemical preparation of a conductive ruthenium oxide surface was presented by Zhang et al [8], and the electrodeposition of copper on oxidized ruthenium is discussed by Guo et al [9].…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable interest at the present time [1][2][3][4][5][6][7][8][9][10][11][12][13] in the possible use of ruthenium as an ultrathin trench liner in damascene copper plating which is currently employed in the microelectronics area for the production of on-chip interconnects. The advantages of ruthenium as a trench liner are that ideally it prevents copper transport from the filled trench into the silicon (thus averting device degradation), it is directly platable (dispensing with the need for a seed layer) and it provides strong adhesion between the electrodeposited copper and the barrier film (which reduces copper electromigration at the Ru/Cu interface).…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of ruthenium as a trench liner are that ideally it prevents copper transport from the filled trench into the silicon (thus averting device degradation), it is directly platable (dispensing with the need for a seed layer) and it provides strong adhesion between the electrodeposited copper and the barrier film (which reduces copper electromigration at the Ru/Cu interface). One of the problems with ruthenium is that the metal is susceptible to oxidation in air and aerated water [7,9,12] so that copper may be plated on to an oxide [2] rather than the metal barrier film. Some authors [2] have suggested that ruthenium oxidation is an advantage in that the oxide plugs the grain boundary diffusion passageways and thus maximizes the diffusion barrier performance of the ruthenium liner.…”
Section: Introductionmentioning
confidence: 99%